(untitled) (International Journal of Physiology, 2020)
Introduction: Initially first year course duration was one and half year. It was used to study these subjects for one & half year, but since 2005-2006, first year duration is reduced to one year; but the syllabus for all three subjects is not altered. The first year curriculum starts in the month of August/September in RGUHS while university examination is held in month of June/July. Actually considering government holidays & other things, the actual working days are almost 11 months. The first year MBBS medical students who have admitted in medical college, they have to study three subjects; Anatomy, Physiology & Biochemistry in I st & IInd Semister. In the present study we focused on finding best teaching aids of class room teaching for making students to understand Physiology better. So if we know learning styles of students, teachers can adopt method of teaching accordingly to improve the academic performance of the students and to make learning more interesting and effective. Material and Method: The present study was undertaken in the Karwar Institute of Medical sciences, Karwar. 150 Ist year MBBS (IInd Term) students & 150 IInd year (III term) MBBS students were included in the study. A questionnaire was prepared having 21 items, the first part of questionnaire included demographic and educational details, while second part was covering the different aspects of teaching aids in the form of opinion by medical students. Results: 85% students were felt that PPT should always combined with other teaching aid and 52% students were not affected by transition from PPT to blackboard teaching due to any external cause. Conclusion: Blackboard + Power point is best teaching aid to understand Physiology better. This result may be due to the fact that deficiency of one teaching aid is compensated by other.